KAJIAN POTENSI SUMBER AIR TANAH UNTUK IRIGASI DI KAWASAN CEKUNGAN AIR TANAH PURWOKERTO-PURBALINGGA BERDASARKAN RESISTIVITAS BATUAN BAWAH PERMUKAAN POTENCY STUDY OF GROUNDWATER RESOURCES FOR IRRIGATION IN PURWOKERTO-PURBALINGGA GROUNDWATER RESERVOIR AREA BASED ON RESISTIVITY OF SUBSURFACE ROCKS FORMATION - , Sehah; , Hartono (Pembangunan Pedesaan, 2010)
Purpose of this research is to interpret model of geological structure and deepness of groundwater aquifer. The research has been done by using Geoelectric of Resistivity method at five locations or trajectories in around the agricultural farm at Kembaran and Kalimanah Subdistricts, because both regions were located in groundwater reservoir area and own the wide agricultural farm. Result indicated that geological structure model of subsurface was consisted of sandy claystone, compacted soil, harsh clayly sandstone, smooth sandstone, compacted gravel and sandstone, and sandstone very harsh. Based on the model deepness data obtained of shallow groundwater aquifer surface was between 0 and 4.33 metres measured from local topography. While deep groundwater aquifer surface was between 26.29 and 56.73 metres with the most potential aquifer formation was smooth sandstone. In general, the groundwater potency in the research area was estimated very good, so that it was suitable for exploration as the irrigation source.